UMPSA students’ experience in dealing with unethical and integrity issues in daily lives - Hadijah, Ahmad (2024)
Obviously, conducting an online assessment has many advantages, such as fast results generated through the use of technology. The method can also save instructors’ time by eliminating the need to mark large volumes of paper. However, we are not discussing how convenient these are for the instructor. It is important to recognise that if they are truly motivated to cheat, then we have not done enough to cultivate ethical literacy for our students. There is a clear perception among students that the online format is not only a modern and accessible assessment method but also a platform where they can exploit possible loopholes, such as engaging in discussion among themselves or consulting online resources for information. If that is the case, they are referred to as academic integrity violators who violate the integrity culture of the university.